2009
DOI: 10.1097/ico.0b013e31818c4d47
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive Keratectomy With Mitomycin-C for Consecutive Hyperopia After Radial Keratotomy

Abstract: PRK with MMC 0.02% for consecutive hyperopia after RK seems to be a safe and effective procedure at least in the short-term period of 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
(27 reference statements)
0
13
0
4
Order By: Relevance
“…Numerous studies have reported the outcome of conventional LASIK 4,5 and PRK 8,12,21,22 to correct myopic or hyperopic regression after RK with variable results. Recently, Ghanem et al 23 have shown encouraging results in 61 eyes with a 2-year follow-up after a WG-PRK with mitomycin C (MMC) for hyperopia post-RK.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the outcome of conventional LASIK 4,5 and PRK 8,12,21,22 to correct myopic or hyperopic regression after RK with variable results. Recently, Ghanem et al 23 have shown encouraging results in 61 eyes with a 2-year follow-up after a WG-PRK with mitomycin C (MMC) for hyperopia post-RK.…”
Section: Discussionmentioning
confidence: 99%
“…In a significant percentage of RK patients, the destabilized cornea caused progressive hyperopia. 5,8,10 Although MMC has been a valuable addition to the PRK procedure, its long-term effects are still unknown. RK patients suffering from this consecutive hyperopia, and a number of RK patients with residual myopia and astigmatism, constitute a group of patients that present a challenge to the refractive surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…5,[8][9][10][11] Combined with better laser and ablation profiles and improved topography and wavefront-guided technology, surface ablation is a viable technique for the repair of post RK induced refractive errors including hyperopia, myopia, and astigmatism. 5,[8][9][10][11] Combined with better laser and ablation profiles and improved topography and wavefront-guided technology, surface ablation is a viable technique for the repair of post RK induced refractive errors including hyperopia, myopia, and astigmatism.…”
mentioning
confidence: 99%
“…167 This has led to extensive use of MMC as an adjuvant drug after PRK to correct residual myopia or hyperopia after radial keratotomy. 93,94,127 Majmudar et al 103 first proposed the use of MMC to treat patients with subepithelial fibrosis secondary to previous PRK and radial keratotomy and reported a significant improvement in corneal clarity with a single, 2-minute intraoperative application of 0.02% MMC.…”
Section: After Prk In Eyes With Previous Radial Keratotomymentioning
confidence: 98%